Zebra Longwing, Heliconius charitonia (Linnaeus) (Insecta: Lepidoptera: Nymphalidae) - Jaret C. Daniels (EDIS)
EENY-428, a 3-page illustrated fact sheet by Jaret C. Daniels, is part of the Featured Creatures collection. It describes this neotropical butterfly with elongated wings and bold yellow stripes that is the state butterfly of Florida — it’s distribution, description, life cycle, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, February 2009.